Sublittoral macrobenthic community along the west coast of Sarawak - Zakirah, Bt Mohamad Taufek (Universiti Malaysia Sarawak (UNIMAS), 2010)
Species diversity, density, distribution and relationship of the macrobenthic communities with environmental parameters in west coast of Sarawak were investigated from 4th to 9th September 2009. Sampling was carried out at 3 transects of between 2 to 20m depth ; Kuala Santunong (S1,S2,S3), Lundu (S4,S5,S6) and Sematan (S7,S8,S9) were chosen as sampling area. Ninety three species wete identified. Polychaetes and crustacean communities representing high density number of the whole macrobenthos. The highest density of macrobentos was recorded at S8, followed by S9 and S6. S6 had the highest diversity index with a value of 1.58. The statistical analysis demonstrated a significant difference between the physico-chemical parameters of each transects. The differences in physico-chemical parameters are responsible for the distribution of macrobenthic community between stations in the sublittoral area of Sarawak west-coast.